Lithuanian Political Parties in the Age of Populism: Content Analysis of the 2016 and 2020 Seimas Election Programmes - Ulinskaitė, Jogilė (Politologija, 2021)
During the spread of populism in politics, we know little about the prevalence of populism in the discourse of Lithuanian political parties. This article presents a content analysis of Lithuanian political parties’ manifestos for the 2016 and 2020 parliamentary elections. The results show that references to the people as a homogeneous unit are relatively widespread, but the number of anti-elitist paragraphs in party programmes is lower. We can divide the parties into three groups according to the level of populism. The most populist parties, located at the fringes of the party system, received little support from the voters in the Seimas elections. Parties that presented relatively high numbers of people-centrist paragraphs and a relatively moderate criticism of the elite proved to be much more successful in the election.